New Media and Democratic Culture: A Study Of Indonesia's Anti-Graft 'Facebook Movement' 2009 As The New 'Non-Party' Politics In Indonesia - Masduki, Masduki (Journal of English and Education (JEE), 2010)
Internet or Social Network Site is a new media facilitating collective action and a "public sphere" for political and social interactions. The Internet is not only a big marketplace. Blogs, wikis and other social networking sites provide a technological basis for grassroots action to coordinate and communicate. Movement of 1,000,000 Facebookers Supporting Chandra Hamzah and Bibit Samad Riyanto in Indonesia 2009, was launched after the two suspended Corruption Eradication Commission (KFK) officers were arrested on suspicion of abuse of power. This, become an interesting new phenomenon in Indonesia. It is an example of wide spread popular support for the anti corruption leaders and the anti graft movement.My paper aims to explore the development of social media in Indonesia and its contribution to implementation of transparency and anti graft movement. Particularly, the paper will identify the role of Facebook in establishing a non political party, online parliament and the future of it in Indonesia as the democratic moslem country in the world.Many active discussions has been generated along 2000s on the topic of social media and its effect on the formation and mobilization of social and political movement. For example, the emergence of the Coffee Party in US. Since 2009, Facebook in Indonesia has played an important role in politics and its importance was first noticed by KPK case. Since then there has been growth in the role of Facebook in political movements. The power of civil society in the form of Facebookers replaces democratic checks and balance which in the real world should be the function of political parties in Indonesian parliament.